KANT'IN AŞKINSAL ÖZNESİNDEN TARİHSEL ÖZNEYE: FOUCAULT PERSPEKTİFİNDEN ESTETİK ÜZERİNE DÜŞÜNMEK. - POLAT, Alper Elvan (Muhakeme Journal)
In Kantian aesthetic tradition, the judgment of taste is grounded in a transcendental subject whose universal faculties generate claims to validity beyond empirical conditions. Immanuel Kant's concept of sensus communis functions as the guarantor of this universality, while the aesthetic subject is conceived as a figure purified of historical determinations and situated within a coherent faculty structure. This foundation has constituted one of the principal bases of modern aesthetic theory. This study seeks to problematize the Kantian conception of subjectivity through Michel Foucault's archaeological and genealogical frameworks. Although Foucault does not develop a systematic theory of aesthetics, his analysis of the historical conditions of subject formation enables a critical reinterpretation of the Kantian subject within an aesthetic context. Drawing on Foucault's notions of epistemic rupture and subjectivation, the study argues that the aesthetic subject is not transcendental but historically constituted. To support this argument, it is acknowledged that Foucault does not construct a unified aesthetic theory; however, his archaeological and genealogical tools can be productively extended to this domain. Accordingly, the concepts of episteme developed in The Order of Things and the analysis of power-knowledge in Discipline and Punish provide an analytical framework for demonstrating how the aesthetic subject is produced in the modern period through institutional practices such as museums, art academies, and critical discourse. From this perspective, beauty is reconfigured not as a universal category derived from the invariant structure of the subject, but as a historically produced form shaped by specific regimes of knowledge and power that simultaneously enable and stabilize particular subject positions. Thus, this study is not a comparative attempt between Kant and Foucault, but rather an inquiry into whether Foucault's thought opens a transformative possibility within the field of aesthetics.